KARAKTER TOKOH DALAM NOVEL LENTERA SENJA KARYA ALFIA RAMADHANI - Sri Sakinah Ulfa; La Yani Konisi; La Ode Syukur (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This research aims to describe the character traits in the novel Lentera Senja by Alfia Ramadhani. This study is categorized as library research using a descriptive qualitative method. The primary data source is the novel Lentera Senja, second edition, published in 2023 by Loveable Publisher in Jakarta, with a total of 280 pages. The research focuses on analyzing the characters’ traits through reading and note-taking techniques. The data were analyzed using an objective approach, describing the findings systematically and accurately based on the textual evidence. The term